2008
DOI: 10.1007/s00540-007-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of landiolol, a β1-adrenoceptor antagonist, stimulate smooth muscle contraction of the rat trachea through the Rho-kinase pathway

Abstract: These results suggest that high concentrations of landiolol could cause airway smooth muscle contraction through the Rho-kinase pathway, but not through the PI response coupled with muscarinic M(3) receptors, 5-HT receptors or the activation of L-type Ca(2+) channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“… 5 The weaker negative inotropic effect was confirmed using isolated perfused guinea pig hearts. 6 In addition, the same team using isolated myocyte and patch-clamp techniques showed that esmolol inhibited both the inward rectifier K+ current and the L-type Ca2+ current, and increased the outward current dose-dependently. In contrast, landiolol had minimal cardiac myocyte effects.…”
Section: Pharmacology Of Landiolol In Humans and Animal Modelsmentioning
confidence: 99%
“… 5 The weaker negative inotropic effect was confirmed using isolated perfused guinea pig hearts. 6 In addition, the same team using isolated myocyte and patch-clamp techniques showed that esmolol inhibited both the inward rectifier K+ current and the L-type Ca2+ current, and increased the outward current dose-dependently. In contrast, landiolol had minimal cardiac myocyte effects.…”
Section: Pharmacology Of Landiolol In Humans and Animal Modelsmentioning
confidence: 99%